2012
DOI: 10.1074/jbc.m111.253658
|View full text |Cite
|
Sign up to set email alerts
|

Dual Specificity of Anti-CXCL10-CXCL9 Antibodies Is Governed by Structural Mimicry

Abstract: Background: Dual-specific antibodies can bind to several antigens via different mechanisms. Results: Mutagenesis of CXCL9/CXCL10 from different species identifies serine 13 as a key residue targeted by anti-human CXCL9/CXCL10 dual-specific scFvs. Conclusion: Structural mimicry between human CXCL9 and CXCL10 governs dual-specific scFv binding. Significance: Dissecting the binding mechanism of dual-specific antibodies is important for the development of this class of antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…they were able to identify antibodies that recognize and inhibit, for example, both CXCR3 ligands CXCL9 and CXCL10, while not interfering with CXCL11. 58,61 Epitope mapping confirmed that the pan-specificity is mediated by structural mimicry. 61 In this context, it is important to distinguish between (1) antibodies recognizing a common conserved sequence or an identical structural epitope that is found in several members of a protein family such as the HER proteins or angiopoietins (structural antibodies are compatible with E. coli expression.…”
Section: Pan-specific and Dual Acting Fab (Daf) Igg Antibodiessupporting
confidence: 59%
See 2 more Smart Citations
“…they were able to identify antibodies that recognize and inhibit, for example, both CXCR3 ligands CXCL9 and CXCL10, while not interfering with CXCL11. 58,61 Epitope mapping confirmed that the pan-specificity is mediated by structural mimicry. 61 In this context, it is important to distinguish between (1) antibodies recognizing a common conserved sequence or an identical structural epitope that is found in several members of a protein family such as the HER proteins or angiopoietins (structural antibodies are compatible with E. coli expression.…”
Section: Pan-specific and Dual Acting Fab (Daf) Igg Antibodiessupporting
confidence: 59%
“…58,61 Epitope mapping confirmed that the pan-specificity is mediated by structural mimicry. 61 In this context, it is important to distinguish between (1) antibodies recognizing a common conserved sequence or an identical structural epitope that is found in several members of a protein family such as the HER proteins or angiopoietins (structural antibodies are compatible with E. coli expression. Nevertheless, using this approach Yu et al designed a bispecific antibody that binds with low affinity to the transferrin receptor (TfR) and with high affinity to the enzyme β-secretase (BACE1).…”
Section: Pan-specific and Dual Acting Fab (Daf) Igg Antibodiessupporting
confidence: 59%
See 1 more Smart Citation
“…IgG-like bispecific constructs have been described that do not comprise regular Fab arms, but engineered arms where two VHH domains are fused to the CH1 and CK constant domains in place of the regular heterodimeric Fv 3 . Finally, a few examples of bispecific Fv regions comprising a VH-VL heterodimer have been reported: Novimmune described engineered Fv regions, each specific for two non-homologous chemokines that are bispecific based on structural mimicry of two targets 4 , 5 , Genentech described dual action Fabs that carry Fv regions with partially overlapping paratopes against two unrelated targets 6 , 7 , and GSK/Domantis, as well as Abbott/AbbVie published Fv regions where the VH and the Vk domains are essentially two distinct single-domain antibodies directed against two different cytokines 8 – 10 .…”
Section: Introductionmentioning
confidence: 99%